Tracking immunization milestones: a community-based survey of child vaccination compliance from birth to one year age in India - Khan, Ayub; Shankar, Hari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Immunization is a crucial public health intervention that significantly reduces childhood morbidity and mortality. In India, despite the efforts of programs like the universal immunization program (UIP), there remain significant challenges in ensuring timely vaccination. This study investigates the compliance with immunization schedules among children in a rural area of Varanasi, India, from birth to one year of age. Methods: A prospective cohort study was conducted from November 2022 to February 2024, involving 150 newborns. The participants included infants delivered via both caesarean section (CS) and vaginal delivery. Monthly delivery lists from the community health centre facilitated the identification and random selection of eligible newborns. The study entailed a baseline visit followed by four quarterly follow-ups over one year. Results: The study revealed significant delays in vaccination timing. Hepatitis B had the highest on-time rate at 99.3%, while rotavirus-1 had the highest delay at 35.5%. Other notable delays included BCG (15.8%) and oral polio vaccine (OPV) birth (25.3%). The on-time rates for subsequent doses of OPV and pentavalent vaccines ranged from 65.9% to 77.7%, with delays observed in about a quarter of the vaccinations. Socio-demographic factors indicated a predominance of joint families (85.3%), with most parents having completed high school or higher education. Conclusions: The findings highlight the need for enhanced strategies to improve adherence to vaccination schedules in rural areas. Significant delays in immunization, particularly for rota-1 and OPV doses, underscore the necessity for targeted interventions.